Emission of Noble Gases Binary Mixtures under Excitation by the Products of the 6Li (n, α)3 H Nuclear Reaction - Kuanysh Samarkhanov; Mendykhan Khasenov; Erlan Batyrbekov; Inesh Kenzhina; Yerzhan Sapatayev; Vadim Bochkov (Science and Technology of Nuclear Installations)
The luminescence of Kr-Xe, Ar-Kr, and Ar-Xe mixtures was studied in the spectral range 300–970 nm when excited by 6Li (n, α)3 H nuclear reaction products in the core of a nuclear reactor. Lithium was deposited on walls of experimental cell in the form of a capillary-porous structure, which made it possible to measure up to a temperature of 730 K. The temperature dependence of the radiation intensity of noble gas atoms, alkali metals, and heteronuclear ionic noble gas molecules was studied. Also, as in the case of single-component gases, the appearance of lithium lines and impurities of sodium and potassium is associated with vaporization during the release of nuclear reaction products from the lithium layer. The excitation of lithium atoms occurs mainly as a result of the Penning process of lithium atoms on noble gas atoms in the 1s states and subsequent ion-molecular reactions. Simultaneous radiation at transitions of atoms of noble gases and lithium, heteronuclear ion molecules of noble gases allows us to increase the efficiency of direct conversion of nuclear energy into light.